2015
DOI: 10.1007/s12035-015-9266-3
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Self-assembling Nanofiber Containing Bone Marrow Homing Peptide’s Motif Induces Motor Neuron Recovery in Animal Model of Chronic Spinal Cord Injury; an In Vitro and In Vivo Investigation

Abstract: To date, spinal cord injury (SCI) has remained an incurable disaster. The use of self-assembling peptide nanofiber containing bioactive motifs such as bone marrow homing peptide (BMHP1) as an injectable scaffold in spinal cord regeneration has been suggested. Human endometrial-derived stromal cells (hEnSCs) have been approved by the FDA for clinical application. In this regard, we were interested in investigating the role of BMHP1 in hEnSCs' neural differentiation in vitro and evaluating the supportive effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…That investigation showed that cell attachment of -BMHP nanofiber was higher than short laminin's motif. Our study also indicated that cell viability of encapsulated cells into -BMHP nanofiber was higher than long laminin's motif [36].…”
Section: Discussionsupporting
confidence: 55%
“…That investigation showed that cell attachment of -BMHP nanofiber was higher than short laminin's motif. Our study also indicated that cell viability of encapsulated cells into -BMHP nanofiber was higher than long laminin's motif [36].…”
Section: Discussionsupporting
confidence: 55%
“…The concept of biomaterials that can be injected and form a defined guidance architecture in situ is attractive; nevertheless, development of such biomaterials has posed a formidable challenge. Promising strategies to overcome this challenge include the use of scaffolds that are based on self-assembling fibers 56,95,124,180 or that are embedded with magnetically responsive microgels. 58 In an interesting study, poly(ethylene oxide-stat-propylene oxide) gels containing supermagnetic iron oxide nanorods were used to help the orientation of nerve extension parallel to the rods that were aligned by using an external magnetic field.…”
Section: Reproduced Withmentioning
confidence: 99%
“…This denotes that D-RADA16 and L-RADA16 are enantiomers. The β-sheet structure is essential for peptides in tissue engineering, as this structure has the ability of nanofiber formation and provides support to the cytoskeleton fiber (38). Previous studies have demonstrated that L-RADA16 can self-assemble into a stable β-sheet structure at physiologic conditions, forming interwoven nanofiber scaffolds that mimic the architecture of the ECM (34,3941).…”
Section: Discussionmentioning
confidence: 99%